ANALISIS PENGARUH PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN, KESEHATAN, DAN INFRASTRUKTUR TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI KALIMANTAN TIMUR: ANALISIS PENGARUH PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN, KESEHATAN, DAN INFRASTRUKTUR TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI KALIMANTAN TIMUR - Endah Susanti (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2020)
This study aims to examine the Effect of Government Expenditur in Educattion sectore,Healthsectore, and Infrastructure sector against Human Develompent Indext (HDI) in East Kalimantan Province during period 2010-2019. This research is a quantitative research to analyze the direct effect of some independent variables and on the dependent variable by using multiple linier regression methode The results of this analysis indicate that government spending education sector (X1) has no significantly affects the Human Development Index (Y) in East Kalimantan Province. Government spending health sector (X2) has significantly affects on the Human Development index (Y) in East Kalimantan Province. Government spending infrastructure sector (X3) has no significantly affects on the Human Development index (Y) in East Kalimantan Province.